2015
DOI: 10.1088/1742-6596/642/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Voyager observations of the magnetic field in the heliosheath and the local interstellar medium

Abstract: Abstract. This paper reviews observations of the magnetic field B in the heliosheath by Voyager 1 (V1) and Voyager 2 (V2) and the recent observations of the LISM by V1. The heliosheath is the region between the termination shock (TS) and the heliopause (HP). The TS was identified by both V1 and V2, and the internal structure of the TS was determined by V2. The radial distance of the TS was 94 AU at V1 and 84 AU at V2, suggesting a global asymmetry of the heliosphere. The average direction of B in the helioshea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…One dealt with CME creation, evolution, and impact on the global structure of the heliosphere (see Burkepile et al, 2004;Gopalswamy (2016); Kilpua et al, 2017and Thompson et al, 2020 for reviews of the research and outstanding questions). A second dealt with the interaction of the solar wind with the interstellar medium: Excellent reviews on that topic can be found (Burlaga, 2015;Burlaga et al, 2018;Zank, 2015). Other topics less extensively mentioned were about shock physics, seed-particle populations, dust, and pickup ions.…”
Section: Discussion: Other Important Questionsmentioning
confidence: 99%
“…One dealt with CME creation, evolution, and impact on the global structure of the heliosphere (see Burkepile et al, 2004;Gopalswamy (2016); Kilpua et al, 2017and Thompson et al, 2020 for reviews of the research and outstanding questions). A second dealt with the interaction of the solar wind with the interstellar medium: Excellent reviews on that topic can be found (Burlaga, 2015;Burlaga et al, 2018;Zank, 2015). Other topics less extensively mentioned were about shock physics, seed-particle populations, dust, and pickup ions.…”
Section: Discussion: Other Important Questionsmentioning
confidence: 99%
“…A spiral magnetic field was observed both inside the heliopause and behind it [41]. The magnetic field of the solar wind is associated with the heliospheric plasma, and the field of the interstellar medium is associated with its plasma.…”
Section: Dynamo Behind the Astrosphere Of A Rapidly Rotating Magneticmentioning
confidence: 94%
“…Observations by the Cassini and Interstellar Boundary Explorer (IBEX) spacecraft revealed specific structures (named "belt" and "ribbon") in energetic neutral atom images, likely produced by charge exchange interactions between solar wind ions and incoming interstellar neutral particles (Funsten et al 2009;Krimigis et al 2009;McComas et al 2009;Schwadron et al 2011;Dialynas et al 2013). Another factor is the expansion of ICMEs over a wide longitudinal range and the merging of successive ICMEs (e.g., Burlaga 2015). The details of all such interactions and evolutions depend on the helio-latitude and helio-longitude.…”
Section: Extending the Interplanetary Scintillation (Ips)-based Solar...mentioning
confidence: 99%